Financial development and tourism at the traditional village in Gianyar, Bali: Tri Hita Karana Value - I Made Suidarma; I Ketut Nurcita; I Dewa Nyoman Marsudiana (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
Tri Hita Karana (THK) is the foundation and guide of the general Hinduism society in living their life. This study aims to identify THK integration on the synergy Village Credit Institution (LPD) and traditional village and observe the LPD contribution in the financial and tourism development at the traditional village in Gianyar, Bali. An ethnography approach was used to identify the problem. The result found that THK has a substantial role in the existence of LPD, which contributes to the traditional village development, especially in Gianyar. The existence of LPD also contributes significantly to the village's financial development, and the existence of LPD could have a significant impact on society’s knowledge and access to financial and services and promoting the regional tourism potential. This effort is also a form of strengthening and maintaining the sustainable existence of traditional village tourism and improving LPD performance in terms of financing and financial management of traditional villages